BEHAVIORAL DETERMINANTS AND PREVENTION OF CHILDHOOD OBESITY (World Bulletin of Public Health, 2026)
Childhood obesity is a chronic, multifactorial disease associated with early cardio metabolic and psychosocial complications. Although genetic, prenatal, and socioeconomic factors contribute to risk, modifiable behaviors—dietary patterns, recreational screen exposure, and insufficient physical activity— play a central role in its development and persistence. An integrated, multi-level approach involving families, schools, and healthcare systems is essential for sustainable outcomes.
Keywords: childhood obesity; overweight; dietary patterns